Barlangklimatológiai mérések két különböző karsztterületen elhelyezkedő magyarországi barlangban - Muladi Beáta (KARSZTFEJLŐDÉS, 2013)
Due to some extreme weather conditions (e.g. droughts, inland waters or floods, etc.), occurring in the Carpathian Basin, climatic fluctuations can be detected in Hungary that can also modify some environmental factors in caves. The study aims at analyzing to which extent surface temperature changes influence cave air temperature. Two different types of caves were selected for the analysis: a tectonically performed epigenetic cave (Hajnóczy Cave) and a typical swallet cave (Trió Cave). Cave air temperature was determined in order to feature the degree of anthropogenic impact, as well as to study the effect of changing surface temperature to the cave air temperature. To test applicability of a wireless sensor network in cave temperature measurement, an UC Mote Mini low power wireless sensor module was used for our measurements. Temperature data were recorded at 10-minute intervals. The obtained data were evaluated using a matrix of correlation coefficients as to identify the communication network between the passages. In the Hajnóczy cave , the average temperature varies between 4.7 to 10.8°C. The daily surface temperature oscillation in the cave still possible to detect at the Almonds .Using the correlation analysis is presented in the Leyla and Almonds data, which show a close relationship with the Housetop data, in both cases, the correlation is 0.88.The human impact on the air temperature of Trió Cave is unambiguous, raising the inside temperature with 0.05°C or 0.6°C in the case of 3 and 28 visitors, respectively.